23rd AIAA Applied Aerodynamics Conference 2005
DOI: 10.2514/6.2005-5216
|View full text |Cite
|
Sign up to set email alerts
|

A Conceptual Design Methodology for Predicting the Aerodynamics of Upper Surface Blowing on Airfoils and Wings

Abstract: One of the most promising powered-lift concepts is Upper Surface Blowing (USB), where the engines are placed above the wing and the engine exhaust jet becomes attached to the upper surface. The jet thrust can then be vectored by use of the trailing edge curvature since the jet flow tends to remain attached by the "Coanda Effect". Wind tunnel and flight-testing have shown USB aircraft to be capable of producing maximum lift coefficients near 10. They have the additional benefit of shielding the engine noise abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…On the basis of existing bibliography it can be possible to conclude that two fluid problems has never been analyzed except by Keen [15,16]. The flow with higher velocity jet over the surface generates the adhesion, while the slower external one increases the complexity and could produce discrepancies into the analysis.…”
Section: Incas Bulletin Volume 6 Issue 1/ 2014mentioning
confidence: 99%
See 4 more Smart Citations
“…On the basis of existing bibliography it can be possible to conclude that two fluid problems has never been analyzed except by Keen [15,16]. The flow with higher velocity jet over the surface generates the adhesion, while the slower external one increases the complexity and could produce discrepancies into the analysis.…”
Section: Incas Bulletin Volume 6 Issue 1/ 2014mentioning
confidence: 99%
“…After these results, it has been possible to obtain an effective model of the nozzle using Bernoulli theorem integral equations and the inviscid irrotational flow hypothesis by Bradshaw [13]. In particular, it takes advantage of the model defined by Keen [14,15], which allow to write a system integral equation, even if approximate. It has been clearly demonstrated that the presence of two streams influences the adhesion of the synthetic fluid stream on two Coanda surfaces, so that the synthetic stream tends to adhere to the surface on the side of the jet with higher momentum.…”
Section: Incas Bulletin Volume 6 Issue 1/ 2014mentioning
confidence: 99%
See 3 more Smart Citations